Cultural Relations and Political Considerations: The British Council in Eastern Europe during the 1980s - Sahel, Malika (European Journal of Social Science Education and Research, 2018)
Established between the Two World Wars in 1934, the British Council was charged to undertake Britain’s cultural relations with other countries. However, its direct involvement and adjustment to Britain’s sudden political decisions, on the international scene, is an indication on the inter-relationship between the British cultural section and the other sections of British foreign policy despite the structural separation of the British Council from British Embassies abroad and the autonomous status this cultural agency was believed to enjoy.